IET electrical systems in transportation (Institute of Engineering and Technology, 2011)
One of 22 internationally renowned Research Journals (formerly IEE Proceedings) published by IET. The journals contain both original and review papers relating to all disciplines in electrical, electronics, computing, control, biomedical and communications technologies.